The Influence Of Brand And Product Packaging On Le Minerale Purchasing Decision On PT. Mayora Indah Tbk in Medan - Munandar, Muhammad Yusril; Nasution, Muhammad Amri; Firah, Al (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Customer purchasing decisions are very important for companies that maintain their business continuity and continuity of business activities. High purchasing decisions from customers who make purchases with an increasing percentage in certain companies rather than other companies. The purpose of this study is to determine and analyze the effect of brand on consumer purchasing decisions. To determine and analyze the effect of product packaging on consumer purchasing decisions on.To determine and analyze the effect of brand and product packaging simultaneously on consumer purchasing decisions. The analysis technique used in this research is quantitative data analysis, namely testing and analyzing data with numerical calculations and then drawing conclusions from these tests with product moment correlation and multiple correlation test tools but in practice the data processing of this study is not processed manually, but using SPSS statistical software. From the results of this study, it is obtained that the significance value of the brand on purchasing decisions based on the t test is obtained at t (count)>t (table) (5.637> 1.66) (Sig 0.001 < α0.05). thus H ois rejected. From the results of this study, the significance value of product packaging based on the t test was obtained as t (count)>t (table) (5.555> 1.66) (Sig 0.000 < α0.05), thus H ois rejected, the conclusion is: there is a significant effect of product packaging on purchasing decisions.Based on the results of the F test above, the value of F (count)>F tableis (17,678> 3.13) (Sig. 0.000 < α0.05) thus H 0is rejected, the conclusion is: there is a significant influence on the influence of brand and product packaging on purchasing decisions.